17β estradiol recruits GluN2B‐containing NMDARs and ERK during induction of long‐term potentiation at temporoammonic‐CA1 synapses. Issue 1 (1st October 2015) - Smith, Caroline C.; Smith, Lindsey A.; Bredemann, Teruko M.; McMahon, Lori L.
Abstract: When circulating 17β estradiol (E2) is elevated to proestrous levels, hippocampus‐dependent learning and memory is enhanced in female rodents, nonhuman primates, and women due to heightened synaptic function at hippocampal synapses. We previously reported that proestrous‐like levels of E2 administered to young adult ovariectomized (OVX) female rats increases the magnitude of LTP at CA3 Schaffer collateral (SC)‐CA1 synapses only when dendritic spine density, the NMDAR/AMPAR ratio, and current mediated by GluN2B‐containing NMDA receptors (NMDARs) are simultaneously increased. We also reported that this increase in GluN2B‐mediated NMDAR current in area CA1 is causally related to the E2‐induced increase in novel object recognition, tying together heightened synaptic function with improved learning and memory. In addition to SC inputs, innervation from the entorhinal cortex in the temporoammonic (TA) pathway onto CA1 distal dendrites in stratum lacunosum‐moleculare is critical for spatial memory formation and retrieval. It is not known whether E2 modulates TA‐CA1 synapses similarly to SC‐CA1 synapses. Here, we report that 24 hours post‐E2 injection, dendritic spine density on CA1 pyramidal cell distal dendrites and current mediated by GluN2B‐containing NMDARs at TA‐CA1 synapses is increased, similarly to our previous findings at SC‐CA1 synapses. However, in contrast to SC‐CA1 synapses, AMPAR transmission at TA‐CA1 synapses is significantly increased, and there is no effect on the LTP magnitude. Pharmacological blockade of GluN2B‐containing NMDARs or ERK activation, which occurs downstream of synaptic but not extrasynaptic GluN2B‐containing NMDARs, attenuates the LTP magnitude only in slices from E2‐treated rats. These data show that E2 recruits a causal role for GluN2B‐containing NMDARs and ERK signaling in the induction of LTP, cellular mechanisms not required for LTP induction at TA‐CA1 synapses in vehicle‐treated OVX female rats. © 2015 Wiley Periodicals, Inc.